VD_FINDINFO HC / 2010 / 112 vom 7. Dezember 2009 - VD Tribunal cantonal (2009)
ENLÈVEMENTINFRACTION, VIOLATION DU DEVOIR D'ASSISTANCE OU D'ÉDUCATION | 183 ch. 1 CP, 219 al. 1 CP, 411 let. h CPP, 411 let. i CPP, 415 CPP